2009
DOI: 10.5194/bg-6-2895-2009
|View full text |Cite
|
Sign up to set email alerts
|

A young afforestation area in Iceland was a moderate sink to CO<sub>2</sub> only a decade after scarification and establishment

Abstract: Abstract. This study reports on three years (2004)(2005)(2006) of measurements of net ecosystem exchange (NEE) over a young Siberian larch plantation in Iceland established on previously grazed heathland pasture that had been scarified prior to planting. The study evaluated the variation of NEE and its component fluxes, gross primary production (GPP) and ecosystem respiration (R e ), with the aim to clarify how climatic factors controlled the site's carbon balance. The young plantation acted as a relatively st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 50 publications
(49 reference statements)
1
9
0
1
Order By: Relevance
“…The R e values measured in the gull colony were among the highest encountered in terrestrial ecosystems in Iceland (e.g. Óskarsson, 1998;Sigurdsson, 2001;Beckmann et al, 2004;Bjarnadottir et al, 2009) and are comparable to maximum values encountered in agricultural croplands and temperate grasslands (Falge et al, 2002) or in fertile Icelandic wetlands (Óskarsson, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…The R e values measured in the gull colony were among the highest encountered in terrestrial ecosystems in Iceland (e.g. Óskarsson, 1998;Sigurdsson, 2001;Beckmann et al, 2004;Bjarnadottir et al, 2009) and are comparable to maximum values encountered in agricultural croplands and temperate grasslands (Falge et al, 2002) or in fertile Icelandic wetlands (Óskarsson, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, carbon cycling in terrestrial ecosystems will be affected by the changing variability of climate (Medvigy et al 2010). Already studies from recent years and decades have suggested that annual carbon budgets of boreal forest ecosystems can be notably influenced by early thaw in spring or warmer than usual autumns (Goulden et al 1998;Piao et al 2008;Bjarnadottir et al 2009), the latter through an increase in ecosystem respiration. Longer-term or delayed effects of these variations are not clear yet, such as the effects on the level of soil CO2 efflux in the following years (e.g.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Egalement, une jeune plantation de mélèze sibérien (Larix sibirica) établie en Islande sur des landes en pâturage s'est avérée être un puits modéré de C 12 ans après boisement, avec une séquestration annuelle de 1,02 t C ha" 1 an" 1 (Bjarnadottir et al 2009). Il ne faut cependant pas oublier que le sol minéral n'est pas inclus dans le présent projet.…”
Section: Réservoirs De Carboneunclassified